Pembelajaran Bahasa Arab Melalui Penggunaan Media Adobe Animate CC di Sekolah - Anwar Sanusi; Fahmi Yahya Abdil Haq (Al-Ma‘rifah, 2021)
The use of learning media is needed in teaching and learning processes so that students can absorb learning materials well and learning activities become more effective. This study aimed to explore teaching and learning Arabic using Adobe Animate CC media in schools. Qualitative method with an ethnography approach was used in this study. Then, the research samples in this study were teachers and 8th grade students of SMPIT Arkan Cendekia, Bekasi City, West Java. The data were collected through interviews, observations, and documentation. The results of this study showed that there were several steps carried out by the teachers in teaching and learning Arabic using Adobe Animate CC, namely (1) lesson planning, (2) learning implementation, and (3) learning evaluation. It was also found that the use of Adobe Animate CC media successfully increased students' learning motivation and students’ Arabic speaking skills. However, there are still some obstacles faced by the teachers in teaching and learning Arabic using these media. Based on the results of this study, it is hoped that it can provide alternative and innovative solutions for teachers in implementing teaching and learning Arabic in the present.